Analisa efektivitas implementasi metode peer tutoring/tutor sebaya terhadap pemahaman konsep matematika siswa - Badriyah, Lailatul (Maliki Interdisciplinary Journal, 2024)
Students’ lack of understanding of mathematical concepts is one of the main problems in mathematics. This is felt by students at various levels. The factors contributing to the emergence of this problem are less interactive learning methods and the weakness of students in remembering the material explained by the teacher, which affects student learning outcomes. In dealing with these problems, teachers have a learning strategy so that students can understand math concepts well by using the peer tutoring method. This research was conducted to analyze the implementation of the peer tutoring method in mathematics learning at all levels of education. This research method uses literature studies from several journal articles related to the implementation of peer tutoring at various levels of education. The results revealed that the implementation of peer tutoring on the understanding of mathematical concepts is effective at all levels of education. This is indicated by an increase in the percentage of students who are complete with various materials in mathematics learning.